Estado de conservación y documentación de las lenguas de América Central pertenecientes a las agrupaciones jicaque, lenca, misumalpa, chibchense y chocó - Constenla Umaña, Adolfo (2012)
This article focuses on the state of conservation and documentation of the indigenous languages of Central America including the linguistic area of Colombia-Central America (parallel to a high degree with the archaeological area called lower Central America), languages all of which belong to one of the following five genealogical families: Jicaquean, Lencan, Misumalpan, Chibchense and Choco.